The determinants of carbon dioxide emissions in Malaysia and Singapore - Norimah Rambeli,; Dayang Affizzah Awang Marikan,; Emilda Hashim,; Siti Zubaidah Mohd. Ariffin,; Asmawi Hashim,; Podivinsky, Jan M. (Penerbit Universiti Kebangsaan Malaysia, 2021)
The focal aim of this paper is to examine the relationship between total energy consumption, Gross Domestic Product, urbanization, trade openness and financial development on carbon dioxide (CO2) emissions. The study focuses on two selected ASEAN countries namely, Malaysia and Singapore, due to their major contribution in CO2 emissions among other ASEAN countries, after Brunei. This study adopts the quarterly time series data from Q1:2010 to Q1:2020. By utilizing the linear ARDL method, the presence of a positive and long-term relationship was confirmed between the variables for both countries. The findings also validate the Environment Kuznets hypothesis namely, that CO2 emissions will continue to rise until the national income reaches optimum point and beyond this environment quality will begin to improve. The results established that financial development helps to reduce CO2 emissions in both the short- and long-run. Further, trade openness tends to reduce CO2 in Malaysia. For Singapore however, it reduces CO2 in the short-run but not in the long-run. In general the study reveals that the relationship between emissions of CO2 and economic development is U-shaped, for both countries. For future sustainable environment the study implies that specific financial planning towards green technology is necessary to sustain a better environment. Economic growth of the country is therefore more meaningful if accompanied with a sustainable environment for future generations.